3D graphene-based hybrid materials: synthesis and applications in energy storage and conversion. Issue 34 (17th August 2016) - Shi, Qiurong; Cha, Younghwan; Song, Yang; Lee, Jung-In; Zhu, Chengzhou; Li, Xiaoyu; Song, Min-Kyu; Du, Dan; Lin, Yuehe
Abstract : Porous 3D graphene-based hybrid materials (3D GBHMs) are currently attractive nanomaterials employed in the field of energy. Abstract : Porous 3D graphene-based hybrid materials (3D GBHMs) are currently attractive nanomaterials employed in the field of energy. Heteroatom-doped 3D graphene and metal, metal oxide, and polymer-decorated 3D graphene with modified electronic and atomic structures provide promising performance as electrode materials in energy storage and conversion. Numerous synthesis methods such as self-assembly, templating, electrochemical deposition, and supercritical CO2, pave the way to mass production of 3D GBHMs in the commercialization of energy devices. This review summarizes recent advances in the fabrication of 3D GBHMs with well-defined architectures such as finely controlled pore sizes, heteroatom doping types and levels. Moreover, current progress toward applications in fuel cells, supercapacitors and batteries employing 3D GBHMs is also highlighted, along with the detailed mechanisms of the enhanced electrochemical performance. Furthermore, current critical issues, challenges and future prospects with respect to applications of 3D GBHMs in practical devices are discussed at the end of this review.